BRAIN DRAIN: A HARSH REALITY. INTERNATIONAL MIGRATION OF PAKISTANI MEDICAL GRADUATES - Imran, Nazish; Azeem, Zahra; Haider, Imran Ijaz; Bhatti, Muhammad Riaz (Journal of Postgraduate Medical Institute, 2011)
Objective: To explore final year students & fresh graduates' intentions to train abroad, identify the Methodology: Following informed consent, respondents were asked to complete a self administered structured questionnaire to collect demographic and educational information, their plans for post graduation training abroad, factors influencing decision to migrate abroad or stay in Pakistan as well as attitudes towards prospects in Pakistan and abroad. Data was entered and analyzed by SPSS 17.0. Results: Among the 275 respondents, 176 (60.4%) intended to go abroad for postgraduate training. Professional excellence (25.5%), easier career settlement(10.2%) and financial prosperity(7.6%) were some of the goals respondents wish to achieve through training abroad while required process of certifications i.e. exams and tests(37.5%), expenses(24.4%) and visa problems(21.5%) were identified as barriers for migration abroad. Agreement among various groups (general public, patients, healthcare institutions, academic community) considering doctors trained abroad as more qualified than doctors trained in Pakistan was noted. Respondents showed dissatisfaction regarding job prospects, career progression, and society and government attitude towards doctors as well as living standards in Pakistan. Positive attitudes were identified towards doctors' status, living standards, and ability to cope with working conditions, political and social circumstances abroad. Conclusion: A significant percentage of medical graduates intend to migrate abroad for post graduate training. Apart from better economic prospects, unhelpful views towards conditions in Pakistan also contribute for increasing trend of migration among physicians from our homeland. influencing factors for this decision and understand their attitudes towards conditions in Pakistan and abroad.